2019
DOI: 10.1111/nyas.14206
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase CHIP in normal cell function and in disease conditions

Abstract: In eukaryotic cells, ubiquitination and proteasomal degradation is an essential mechanism for regulating protein functions. For example, critical signaling proteins play their roles by controlling different cellular functions. Once a signaling protein has been activated, its activity needs to be quickly downregulated by different mechanisms, including ubiquitination/proteasome regulation. Failure to regulate the activity or expression levels of these proteins may cause human diseases. Protein ubiquitination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 73 publications
(95 reference statements)
0
31
0
Order By: Relevance
“…One prime example of such ligases is CHIP encoded by the STUB1 gene and whose genomic alterations cause spinocerebellar ataxia ( Shi et al, 2013 ). Thanks to its ability to bind to cellular chaperones such as HSP70 and HSP90, CHIP mediates the ubiquitination of misfolded proteins, thereby targeting them for subsequent degradation by 26S proteasomes ( Edkins, 2015 ; Wang et al, 2020 ). Such misfolded proteins typically encompass defective ribosomal products (DRIPS) which are generated during protein biosynthesis as a consequence of ribosomal mistranslation ( Yewdell et al, 1996 ).…”
Section: E3 Ubiquitin Ligases and Protein Aggregation In Nddmentioning
confidence: 99%
“…One prime example of such ligases is CHIP encoded by the STUB1 gene and whose genomic alterations cause spinocerebellar ataxia ( Shi et al, 2013 ). Thanks to its ability to bind to cellular chaperones such as HSP70 and HSP90, CHIP mediates the ubiquitination of misfolded proteins, thereby targeting them for subsequent degradation by 26S proteasomes ( Edkins, 2015 ; Wang et al, 2020 ). Such misfolded proteins typically encompass defective ribosomal products (DRIPS) which are generated during protein biosynthesis as a consequence of ribosomal mistranslation ( Yewdell et al, 1996 ).…”
Section: E3 Ubiquitin Ligases and Protein Aggregation In Nddmentioning
confidence: 99%
“…In cancer the pathogenic mechanisms of CHIP are less clear (216). Several studies on breast cancer cells have indicated CHIP as tumor suppressor (212,(217)(218)(219).…”
Section: Chip and Ghrmentioning
confidence: 99%
“…A typical example of U-box-type ubiquitin ligase is the C terminus of the Hsc70-interacting protein (CHIP) [26]. Upon heat stress, CHIP recognizes its substrates in the context of activated heat shock proteins, controlling the stability and fate of misfolded proteins.…”
Section: The Ubiquitin–proteasome Systemmentioning
confidence: 99%